The retrieval of perceptual memory details depends on right hippocampal integrity and activation. (November 2016) - St-Laurent, Marie; Moscovitch, Morris; McAndrews, Mary Pat
Abstract: We assessed whether perceptual richness, a defining feature of episodic memory, depends on the engagement and integrity of the hippocampus during episodic memory retrieval. We tested participants' memory for complex laboratory events (LEs) that differed in perceptual content: short stories were either presented as perceptually rich film clips or as perceptually impoverished narratives. Participants underwent functional magnetic resonance imaging ( f MRI) while retrieving these LEs (narratives and clips), as well as events from their personal life (autobiographical memories). In a group of healthy adults, a conjunction analysis showed that both real-life and laboratory memories engaged overlapping regions from an autobiographical memory (AM) retrieval network, indicating that laboratory memories mimicked autobiographical events successfully. A direct contrast between the film clip and the narrative laboratory conditions identified regions activated by the retrieval of perceptual memory content, which included the right hippocampus, parahippocampal gyrus, middle occipital gyrus and precuneus. In individuals with medial temporal lobe epilepsy (mTLE) originating from the right hippocampus, the magnitude of this "perceptually rich" signal was reduced significantly, which is consistent with evidence of reduced perceptual memory content in this clinical population. In healthy controls, right hippocampal activation also correlated positively with a behavioral measure of perceptual content in the clip condition. Thus, right hippocampal activity contributed to the retrieval of perceptual episodic memory content in the healthy brain, while right hippocampal damage disrupted activation in regions that process perceptual memory content. Our results suggest that the hippocampus contributes to recollection by retrieving and integrating perceptual details into vivid memory constructs.